Hysterectomy via transvaginal natural orifice transluminal endoscopic surgery versus single‐port laparoscopy: Comparison of early outcomes. Issue 9 (30th June 2021) - Basol, Gulfem; Cora, Ayfer Ozer; Gundogdu, Elif Cansu; Mat, Emre; Yildiz, Gazi; Kuru, Betul; Uzun, Navdar Dogus; Uzel, Kemine; Usta, Taner; Kale, Ahmet
Abstract: Aim: The study objective was to compare intraoperative and early postoperative outcomes among patients who underwent hysterectomy via transvaginal natural orifice transluminal endoscopic surgery (and single‐port lararoscopy for presumed benign gynecologic disorders). Methods: We retrospectively reviewed 40 patients who underwent single‐port laparoscopic hysterectomy and 20 patients who underwent hysterectomy via natural orifice transluminal endoscopic surgery. Patients' age, body mass index, history of previous delivery and surgery, total operation time (from skin incision to closure), intraoperative and postoperative complications conversion to another surgical procedure, drop of hemoglobin level, postoperative pain at 1 and 18 h, average hospital stay, and clinical outcomes were analyzed. Results: Hysterectomy via transvaginal natural orifice transluminal endoscopic surgery was superior to single‐port hysterectomy concerning the length of hospitalization ( p < 0.001) and visual analog scale at 1 h ( p = 0.024) and 18 h ( p < 0.001). In transvaginal natural orifice transluminal endoscopic group, postoperative complications were lower than single‐port laparoscopy group ( p = 0.023). In transvaginal natural orifice transluminal endoscopy, group conversion to a standard vaginal hysterectomy occurred in two cases (10%). Four patients in the single‐port laparoscopic hysterectomy group had umbilical herniation, three had port‐site infections, and two patients had vaginal cuff hematoma. These patients required rehospitalization. Conclusions: Despite hysterectomy via transvaginal natural orifice transluminal surgery has not yet found its place in routine practice in gynecology departments, it could be a prominent alternative approach to other minimally invasive surgical procedures in selected patients with many advantages including lesser pain and lower complication rates compared with single‐port laparoscopic hysterectomy.